Effect of Implementation of the Rapid Response Nursing Team On Outcome Multiple Trauma(Head Trauma And Penetrate Trauma): A clinical trial - Mohammad Ali Soleimani; Zakariya Fattahi; Leili Yekefallah; Mehdi Ranjbaran (Hamadan University of Medical Sciences, 2023)
Background and Objective: Trauma patients admitted to the emergency department are exposed to the risk of clinical conditions and care disorders, which require careful examination and appropriate measures to prevent care disorders and risky situations. The present study aimed to determine the effect of the implementation of the rapid response nursing team on the outcome of multiple trauma patients (head trauma and open trauma) referred to the emergency department. Materials and Methods: This quasi-experimental intervention research was carried out by This semi-experimental interventional research by the rapid response nursing team with the presence of two team members in each shift in the Emergency Department of Taleghani Medical Education Center in Kermanshah on 280 patients referred to the emergency department by non-random allocation method in two groups (control: 140, intervention: 140). In the control group, patients were evaluated and cared for according to the routine of the emergency department. In the intervention group, the rapid response nursing team was put into action. The patients who met the inclusion criteria were accurately triaged and leveled upon arrival. Thereafter, immediately after being admitted to the emergency room, according to priority and level determination, all admitted patients were evaluated and monitored again in terms of consciousness level, vital signs, and clinical status in short rounds. Patients with a low triage level and the need for special care were subjected to continuous monitoring and necessary measures in a timely and fast manner until the final determination. The outcome and results of the measures were recorded for both groups. A researcher-made data collection form was used to collect data. In the end, the data were analyzed using SPSS software (version 25). To compare the quantitative and qualitative outcomes of the two control and intervention groups, independent t-tests and chi-square tests were used, respectively. Results: There was a significant relationship between the establishment of a rapid response nursing team and the outcome of multiple trauma patients (P=0.027). More than twice as many patients in the control group as in the intervention group were transferred to the special ward (P=0.010). The triage level of patients in the intervention group increased significantly (P<0.001). The length of stay of patients in the emergency department decreased (P<0.001). In the intervention group, the success rate of code 99 increased significantly (P=0.015). Among the other study results, we can mention a reduction in mortality and code 99 and an increase in the discharge rate. Conclusion: Considering the favorable effects of the rapid response nursing team on the rate of death, cardio-respiratory arrests, and unwanted consequences, these consequences can be controlled by deploying this team in emergency centers.